Global prevalence of dental caries in the older people, 1991 to 2024: a systematic review and meta-analysis - Yasaman Almasvandi; Narges Ziaei; Mohsen Kazeminia; Parvin Abbasi (Saudi Dental Journal)
Abstract Background Oral health is an integral part of the overall health of the elderly, significantly impacting their physical, social, and psychological well-being. This study aimed to synthesize, summarize, and standardize the results of primary studies, resolve inconsistencies, examine the influence of potential factors, and estimate the global prevalence of dental caries in the elderly through a systematic review and meta-analysis. Methods The systematic review and meta-analysis covered studies published from 1991 to November 2024. Relevant articles were identified through searches in international databases, including Embase, PubMed, Scopus, and Web of Science (WoS), using appropriate keywords. The quality of the studies was assessed using the Joanna Briggs Institute (JBI) checklist. Heterogeneity among studies was evaluated using the I2 statistic. Data were analyzed using Comprehensive Meta-Analysis software, version 2. Results The initial search yielded 20,374 studies, of which 31 articles with a total sample size of 26,703 individuals met the inclusion criteria for the meta-analysis. The global prevalence of dental caries in the elderly was estimated at 60.7% (95% confidence interval: 54.6%–66.4%). The highest prevalence was observed in the Americas at 79.6% (95% CI: 34.8%–96.6%). Meta-regression analysis revealed that the prevalence of dental caries decreased with larger sample sizes, higher study quality, and older age, while it increased over time (P < 0.05). Conclusion The findings indicate a high prevalence of dental caries among the elderly, particularly in the Americas, with an upward trend in recent years. It is recommended that health policymakers prioritize prevention and control measures for this condition.